2009
DOI: 10.1021/jp8073915
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Phase Coexistence, Critical Properties, and Surface Tension of Confined Alkanes

Abstract: Configurational-bias grand-canonical transition-matrix Monte Carlo simulations are conducted to investigate various thermophysical properties, such as phase coexistence, critical properties, density and orientation profiles of liquid and vapor phases, and vapor-liquid surface tension of methane, ethane, propane, n-butane, and n-octane in bulk and slit pores of graphite and mica surfaces. An exponential-6 (exp-6) model is used for the investigation of normal alkanes with a cutoff radius, 15 Å. It is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
216
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(232 citation statements)
references
References 66 publications
16
216
0
Order By: Relevance
“…We have also recently shown that such two linear regimes for the shift in the critical temperature in slit pores generally holds for normal alkanes. 60 We further studied the structural behavior of the coexisting phases to understand the behavioral change in the critical temperature shift. Figures 5͑a͒ and 5͑b͒ present the density profile of the coexistence vapor and liquid phases for the fluid interaction range = 3.0 at a reduced temperature, T R = T / T c,pore = 0.7, for various slit pores.…”
Section: A Phase Diagram Under Confinementmentioning
confidence: 99%
“…We have also recently shown that such two linear regimes for the shift in the critical temperature in slit pores generally holds for normal alkanes. 60 We further studied the structural behavior of the coexisting phases to understand the behavioral change in the critical temperature shift. Figures 5͑a͒ and 5͑b͒ present the density profile of the coexistence vapor and liquid phases for the fluid interaction range = 3.0 at a reduced temperature, T R = T / T c,pore = 0.7, for various slit pores.…”
Section: A Phase Diagram Under Confinementmentioning
confidence: 99%
“…A few studies dealing with the adsorption and static properties of confined hydrocarbon liquid films have been reported [20][21][22][23]; however, there is only limited research on the mass transfer of alkanes inside the carbonaceous substrate, in spite of its immediate relevance to applications. The MD simulations conducted by Supple and Quirke [24] show a rapid decane imbibition (6445 m/s) along the inner surface of a (13,13) carbon nanotube (CNT) at 298 K, and the penetration length is linearly dependent on time.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Severson and Snurr (2007) studied the adsorption isotherms of linear alkanes (ethane, pentane, decane, and pentadecane) on activated carbon and evaluated the functions of slit size, chain length, and temperature on adsorption. Furthermore, it was disclosed by Singh et al (2009) that the thermophysical properties of alkanes under confinement of nanopores, including vapor-liquid phase coexistence, critical properties, and surface tension, show dramatic distinction from bulk values. Most recently, to understand the effect of carbonaceous deposits on the performance of a spark-ignition engine, Harrison et al (2014) studied the singlecomponent adsorption of normal and branched alkanes in slits with different apertures (1, 2, and 4 nm) at 390 K. They concluded that the preferential adsorption of i-octane was enhanced substantially in smaller pores due to packing effects.…”
Section: Introductionmentioning
confidence: 99%
“…(2) the temperatures and pressures in previous studies were either too high (1500 K, 600 MPa (Severson and Snurr, 2007); 560 K (Singh et al, 2009)) or too low (293 K, 10 kPa (Do and Do, 2005); 300 K, 100 kPa (Severson and Snurr, 2007); 3 MPa (Harrison et al, 2014)) to represent the conditions in shale reservoirs; and (3) the adsorption of alkanes in carbonaceous slits with apertures greater than 5 nm\ \the common sizes in shale\ \has not been reported.…”
Section: Introductionmentioning
confidence: 99%